Countrywide natural experiment links built environment to physical activity - Tim Althoff; Boris Ivanovic; Abby C. King; Jennifer L. Hicks; Scott L. Delp; Jure Leskovec (Nature, 2025)
Abstract While physical activity is critical to human health, most people do not meet recommended guidelines 1,2 . Built environments that are more walkable have the potential to increase activity across the population 3–8 . However, previous studies on the built environment and physical activity have led to mixed findings, possibly due to methodological limitations such as small cohorts, over-reliance on self-reported measures and cross-sectional designs 5,7,9–11 . Here we address these limitations by leveraging a large US cohort of smartphone users ( N = 2,112,288) to evaluate within-person longitudinal behaviour changes that occurred over 248,266 days of objectively measured physical activity across 7,447 relocations among 1,609 US cities. By analysing the results of this natural experiment, which exposed individuals to differing built environments, we find that increases (decreases) in walkability are associated with significant increases (decreases) in physical activity after relocation. For example, moving from a less walkable (25th percentile) city to a more walkable city (75th percentile) increased walking by 1,100 daily steps, on average. These changes hold across different genders, ages and body mass index values, and are sustained over 3 months. The added activity is predominantly composed of moderate-to-vigorous physical activity, which is linked to an array of associated health benefits 1 . Evidence against residential self-selection confounding is reported. Our findings provide robust evidence supporting the importance of the built environment in directly improving health-enhancing physical activity and offer potential guidance for public policy activities in this area.